Soil Water Availability Changes in Amount and Timing Favor the Growth and Competitiveness of Grass Than a Co-dominant Legume in Their Mixtures - Xu, Weizhou; Deng, Xiping; Xu, Bingcheng; Palta, Jairo A.; Chen, Yinglong (Frontiers in Plant Science, 2021)
Grasslands on the semiarid Loess Plateau of China are expected to be particularly responsive to the size and frequency changes of extreme precipitation events, because their ecological processes are largely driven by distinct soil moisture pulses. However, the plant growth and competitiveness of co-dominant species in response to soil water changes in the amount and timing are still unclear. Thus, two co-dominant species, Bothriochloa ischaemum and Lespedeza davurica, grew at seven mixture ratios under three watering regimes [80±5% pot soil capacity (FC) (High watering), 60±5% FC (Moderate watering) and 40±5% FC (Low watering)] in a pot experiment. Soil water contents were rapidly improved from low to moderate water, and from moderate to high water, respectively, at the heading, flowering and maturity stages of B. ischaemum, and maintained until the end of the growing season of each species. Biomass production of both species increased significantly with increased soil water contents, particularly at heading and flowering periods with more pronounced increase in B. ischaemum in mixtures. Root/shoot ratio of both species was decreased when soil water availability increased at heading or flowering periods. Total biomass production, water use efficiency (WUE) and relative yield total (RYT) increased gradually with the increase of B. ischaemum in mixtures. Relative competition intensity was below zero in B. ischaemum, and above zero in L. davurica. Competitive balance index calculated for B. ischaemum was increased with the increase of soil water contents. B. ischaemum responded more positively to the periodical increase in soil water availability than L. davurica, indicating that the abundance of B. ischaemum could increase in relatively wet seasons or plenty-rainfall period. In addition, the mixture ratio of 10:2 (B. ischaemum to L. davurica) was the most compatible combination for improved biomass production, WUE and RYTs across all soil water treatments.